Comprehensive board diversity and quality of corporate social responsibility disclosure: evidence from an emerging market - Nooraisah Katmon (Tanjong Malim, 2019)
Comprehensive board diversity and quality of corporate social responsibility disclosure: evidence from an emerging market by Nooraisah Katmon